Tsunami hazard from the subduction megathrust of the South China Sea : Part I. source characterization and the resulting tsunami - Megawati, Kusnowidjaja (2012)
The subduction megathrust under the Manila Trench has been accumulating strain over a period of 440 years or more, and could be the source for a giant earthquake of Mw ∼ 9. We present a plausible earthquake rupture model constructed from seismic and geodetic data, together with hydrodynamic simulations of the potential tsunami with COMCOT (COrnell Multi-grid COupled Tsunami model). Results indicate that this megathrust poses a risk of devastating tsunami for the Philippines, southern China, Vietnam and other population centers bordering the South China Sea.